2010
DOI: 10.1007/s00467-009-1428-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hyponatremia in children with gastroenteritis treated with hypotonic intravenous fluids

Abstract: Hypotonic saline solutions have been used for over five decades to treat children with diarrheal dehydration. However, concern has recently been raised about the potential for iatrogenic hyponatremia as a result of this therapy. We reviewed the medical records of 531 otherwise healthy children with gastroenteritis who had been admitted to the hospital for intravenous fluid therapy. We retrospectively collected data on 141 of these children who had received two serum electrolytes (one upon admission and the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
5
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 14 publications
1
36
5
6
Order By: Relevance
“…26,27,39 Many observational studies suggested that isotonic fluids are superior to hypotonic fluids in hospitalized children. [17][18][19][40][41][42] These studies were not included in the current meta-analysis because they did not meet the predefined criteria. However, the findings from these studies are consistent with our findings.…”
Section: Figurementioning
confidence: 99%
“…26,27,39 Many observational studies suggested that isotonic fluids are superior to hypotonic fluids in hospitalized children. [17][18][19][40][41][42] These studies were not included in the current meta-analysis because they did not meet the predefined criteria. However, the findings from these studies are consistent with our findings.…”
Section: Figurementioning
confidence: 99%
“…Hyponatremia (Na <135 mEq/L) was observed in 19 % of children who received hypotonic IV fluid for isonatremic dehydration associated with gastroenteritis [32]. Both febrile children and those with gastroenteritis have been shown to have inappropriately elevated ADH levels [17].…”
Section: Fluid Tonicity and Hyponatremiamentioning
confidence: 99%
“…Additionally, obstructive hydrocephalus and < 3.5 years of age were identified as significant independent risk factors for severe hyponatremia among those affected. The risk for hospital-acquired hyponatremia and hyponatremic encephalopathy have been related to the use of hypotonic intravenous solutions [6,[70][71][72][73][74][75][76][77] . Wang et al [78] found a significantly higher risk for hyponatremia and severe hyponatremia among pediatric patients administered hypotonic solutions compared with isotonic fluids in a systematic review of ten randomized clinical trials involving 855 subjects.…”
Section: Childrenmentioning
confidence: 99%